Biodiversity Literacy and Tradition: Development of Student Worksheets Based on the Local Potential of the Indahan Tupporobu Dish for Biology Learning - Nurul Faizah Siregar; Amprasto; Siti Sriyati (Faculty of Tarbiyah and Teacher Training UIN Jurai Siwo, Lampung, 2025)
Indonesia is a country with high levels of biodiversity (megabiodiversity), but student literacy related to biodiversity is still relatively low. This study aims to describe the feasibility, practicality, and effectiveness of Student Worksheets based on local potential, which are expected to improve student learning outcomes in biodiversity literacy. This study involved students from SMAN 4 Padangsidimpuan, grade X. This research is a Research and Development (R&D) study that adapts the 4D model from Thiagarajan, Semmel, and Semmel, which consists of the Define, Design, Develop, and Disseminate stages. However, this study was only conducted up to the Development stage due to time constraints. The Student Worksheets developed was verified by subject matter experts, with verification results showing a very high level of validity and no need for revision, namely 84% by subject matter experts and 85% from the analysis of student response test results, categorized as very good. The effectiveness test results showed that the Student Worksheets based on local potential is effective in improving students' biodiversity literacy, with an N-gain value of 0.36 (moderate category). Therefore, this Student Worksheets is suitable for use as a learning tool in biology education, particularly for topics related to biodiversity.